Automated Design Methodology for Electromagnetic Energy Harvesters - Bianca Leistritz; Ludwig Herzog (Sensors)
An automated design methodology for electromagnetic harvesters is necessary for the cost-effective design of adapted energy harvesters to be used in application-specific requirements. With the help of the automated design methodology presented in this paper, application-specific designs can be generated quickly and easily, and systematic comparisons between the structures can be made to select the best suited harvester structure. For the dimensioning of the design parameters, both analytical approximation formulas and models for coupling with field calculations were implemented. An exemplary structure comparison based on three scenarios shows the advantageous suitability of one topology in large areas of the aspect ratio.